PET and SPECT of Neurobiological Systems 2014
DOI: 10.1007/978-3-642-42014-6_14
|View full text |Cite
|
Sign up to set email alerts
|

PET and SPECT Imaging of Steroid Hormone Receptors

Abstract: Steroid hormones like estrogens, progestins, androgens, and corticosteroids are involved in normal brain function. They are able to exert both neuroprotective and neurotrophic effects. In addition, steroid hormones play a crucial role in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 141 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…16β-[ 18 F]fluoro-5α-dihydrotestosterone ([ 18 F]FDHT) is an 18 F-labeled androgen derivative that has been used successfully as a PET tracer for imaging of AR expression in rats, baboons and patients with prostate cancer. However, there are no studies reported yet on the use of [ 18 F]FDHT PET for imaging of AR expression in the brain [8]. The aim of this study was therefore to investigate the feasibility of AR imaging in the rat brain using [ 18 F]FDHT PET.…”
Section: Introductionmentioning
confidence: 98%
“…16β-[ 18 F]fluoro-5α-dihydrotestosterone ([ 18 F]FDHT) is an 18 F-labeled androgen derivative that has been used successfully as a PET tracer for imaging of AR expression in rats, baboons and patients with prostate cancer. However, there are no studies reported yet on the use of [ 18 F]FDHT PET for imaging of AR expression in the brain [8]. The aim of this study was therefore to investigate the feasibility of AR imaging in the rat brain using [ 18 F]FDHT PET.…”
Section: Introductionmentioning
confidence: 98%